Little Town of Bethlehem . - CTVC London, SE1 2LH (London CTVC, 2008)
This Christmas special travels to Bethlehem to meet today’s shepherds, wise men, innkeepers and “angels” to see how the original Nativity Story inspires Bethlehem’s under-threat Christian Community. Can a 2,000 year old story inspire people caught up in the violence of the Middle East ? The programme includes carols from The Lutheran Christmas Church in Bethlehem, as well as extracts from the Nativity Story read by young Palestinian Christians.

- http://www.ctvc.co.uk
Palestine - 2007
Documentary
English
"TX version with BITC"